Micronutrients Levels in Sensorineural Hearing Loss - Vhaishakh Nayar; Raveena Prasad; Mridhula R. Menon; Vadisha Bhat; Prajna Bhandary; Sharmila K. Poonacha (Journal of the Scientific Society)
Background: This study is conducted to estimate the serum levels of Magnesium and Zinc levels in patients with sensorineural hearing loss. Aim: To find the association between serum concentrations of Magnesium and Zinc and sensorineural hearing loss. Materials and Methods: Subjects diagnosed with sensorineural hearing loss following pure-tone audiometry were included in the study. Based on the severity of hearing loss, subjects were classified into Grade I (25–40 dB HL), Grade II (41–70 dB HL), and Grade III (>70 dB HL). Blood was collected after obtaining informed consent, serum was processed with a semi-autoanalyzer, and the results were analyzed. Results: Of the 84 subjects included in the study, 31 were found to have Grade I, 37 Grade II, and 16 to have Grade III hearing loss. A decreasing trend was noted in serum concentration of Magnesium with increasing severity of hearing loss; the average concentration in Grade I was 2.18, in Grade II was 2.16, and in Grade III was 2.13 mg/dl. The serum concentration of Zinc also shows a decreasing trend with increasing hearing loss. Grade I subjects have an average Zinc concentration of 79.17, decreasing to 77 in Grade III hearing loss. Even with the decreasing trend, the variation between Serum Magnesium and Zinc values among the three groups was insignificant, with a P = 0.064 for Magnesium and 0.89 for Zinc. Conclusion: A decrease in serum concentration of Magnesium and Zinc is associated with an increase in the severity of sensorineural hearing loss.